1992
DOI: 10.1002/jlb.52.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neutrophil leukocyte secretory response to fMLP in whole blood in vitro

Abstract: A simple, precise method has been developed for assessing neutrophil secretory responses (release of vitamin B12 binding protein from specific granules) to challenge of aliquots of whole blood with the bacterial chemotactic peptide N-formylmethionyl-leucyl-phenylalanine (fMLP). Dose-response studies performed on blood from normal healthy volunteers showed higher maximal secretory responses in males than females (33.3 +/- SEM 2.2 vs. 27.4 +/- 2.5, P less than .005) a left shift in dose-response curves after fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In accordance with a study of Fearon and Collins [22], this up-regulation was maximal at a concentration of 0-02 /IM fMLP. Since the CDllb is localized in the specific granules of neutrophils [26], this result is consistent with the findings that the maximal release of vitamin B12 binding protein [27] and maximal chemotaxis [28] occur at 0-01 //H of fMLP.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with a study of Fearon and Collins [22], this up-regulation was maximal at a concentration of 0-02 /IM fMLP. Since the CDllb is localized in the specific granules of neutrophils [26], this result is consistent with the findings that the maximal release of vitamin B12 binding protein [27] and maximal chemotaxis [28] occur at 0-01 //H of fMLP.…”
Section: Discussionsupporting
confidence: 89%
“…During transmigration, leukocytes express their state of activation by biochemical changes, including degranulation with release of proteolytic enzymes (e.g., elastase, myeloperoxidase), and leading to interstitial inflammation, capillary compression, and reduced perfusion. 22,24 It was demonstrated that heparin preparations inhibit heparinase-mediated degradation of heparan-sulfate moieties of the extracellular matrix, inhibit the migration of leukocytes to extracellular sites, and prevent acute inflammation. 25,26 In our experimental model, each of the above mechanisms may play a role in improved capillary perfusion after enoxaparin injection.…”
Section: Discussionmentioning
confidence: 99%
“…It can, however, elicit neutrophil chemotaxis across epithelial monolayers in vitro (40) and increase permeability and blood flow in the rat small intestine (41). Neutrophil activation may be augmented by other bacterial products (42), and IL-8 expression by neutrophils is significantly enhanced by the addition of LPS (16), suggesting a synergistic response. Therefore, fMLP secreted from H. pylori may permeate the gastric mucosa via damaged epithelial cells and, in the presence of other chemoattractants, potentiate chemotaxis and the activation of neutrophils.…”
Section: Discussionmentioning
confidence: 99%